A DECADE OF PROGRESS: A BIBLIOMETRIC ANALYSIS OF GREEN SAFETY AND HEALTH AND SUSTAINABILITY PERFORMANCE, 2016 – 2025 - Maryam Jamilah Asha’ari,; Nur Afiqah Muhammad Ishak,; Salina Daud,; Rosmah Mat Isa,; Mazzlida Mat Deli,; Ummu Ajirah Abdul Rauf,; Wan Noordiana Wan Hanafi, (PEOPLE: International Journal of Social Sciences, 2025)
In recent years, there is a substantial increase in research on green safety and health and its impact on sustainability performance. However, the evolution and performance patterns of this field are not thoroughly studied. This study uses a comprehensive bibliometric analysis to investigate global research trends in green safety and health in relation to sustainability performance over a ten-year period. Articles published between 2016 and 2025 are extracted from the Web of Science (WoS) core collection, forming a dataset that reflects the expanding scholarly interest in this field. VOSviewer is used to analyse co-authorship networks among authors, institutions, and countries, as well as to map keyword co-occurrence patterns across the decade. This study findings enhance our understanding of the research landscape in this field and offer valuable insights for future studies. Future studies could examine how the latest technology enhances green safety and health for organisation sustainability performance.